Upaya Penerapan Self Love Untuk Membangun Karakter Positif Pada Remaja Di Era Revolusi Society 5.0 - Tirenia Thesalonica Kuway (Jurnal Ilmiah Multidisiplin Keilmuan Mandira Cendikia, 2024)
Loving oneself is a controversial construct: Throughout history, views on self-love have been polarized into "good" (associated with well-being and health) versus "bad" (linked to narcissism and selfishness). While often conflated in academic literature, self-love and narcissism are actually opposites. We aim to address limitations of previous research and propose a methodologically sound model of self-love, arguing that therapists benefit from diverse understandings. The research's goal is to explore how the implementation of self-love contributes to building positive character in adolescents in the era of the 5.0 revolution. Using a qualitative approach and data collection through observation and interviews, the study aims to ascertain the impact of applying self-love in fostering positive character among adolescents in the 5.0 revolution era. The researcher hopes this study will be helpful, beneficial, and serve as a reference for future research.